CBMT-21. TERT PROMOTER-MUTANT GLIOBLASTOMAS EXHIBIT DEPENDENCY ON TELOMERASE. (11th November 2019) - Aquilanti, Elisa; Baird, Duncan; Watson, Jacqueline; Meyerson, Matthew
Abstract: TERT promoter mutations are among the most common somatic alterations in cancer and they occur in about 80% of IDH-wildtype glioblastomas. TERT promoter mutations were found to reactivate telomerase by providing a novel binding site for the GABP transcription factor. While the effects of telomerase ablation are well understood in mice and somatic human cells, these effects in cancer are yet to be fully elucidated. In this study, we used a genetic approach with CRISPR-interference to knock down telomerase in TERT promoter-mutant glioblastoma cell lines. We show that this leads to a gradual and significant reduction in proliferation. This phenotype ultimately culminates in telomere crisis, with telomere shortening, activation of the DNA damage response pathway and formation of chromatin bridges. These data suggest that anti-telomerase therapy is a potential effective approach for glioblastoma tumors.